Temporal variation of picoplankton in the spring bloom of Yellow Sea, China - Zhao, Yuan; Zhao, Li; Xiao, Tian; Liu, Chenggang; Sun, Jun; Zhou, Feng; Liu, Sumei; Huang, Lingfeng; 黄凌风 (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
973 project [2006CB400604, 2011CB409804]; NSFC project [41121064] Temporal variation of Synechococcus, picoeukaryote and heterotrophic bacteria abundance and depth integrated biomass during three spring blooms in 2007 and 2009 were investigated in the Yellow Sea, China. Synechococcus and picoeukaryote responded differently to different types and course of spring blooms. During the diatom blooms of 2007 and Bloom B20 in 2009, Synechococcus and picoeukaryote abundances decreased sharply during the bloom period. However, during a mixed dinoflagellate and diatom bloom of Bloom B23 in 2009, Synechococcus and picoeukaryote increased in abundance and biomass along the bloom. During all three spring blooms, heterotrophic bacteria biomass had a similar increasing trend. Ciliate and heterotrophic nanoflagellate grazing could be responsible for Synechococcus and picoeukaiyote abundance and biomass decrease during the spring blooms. (C) 2013 Elsevier Ltd. All rights reserved.